Global Research Trends in Diagnosis-Related Groups (DRG) and Health Payment Reform: A Bibliometric Analysis (2016–2025) - Ida Ayu Agung Dewi Sawitri; Qurratul Aini (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Healthcare systems globally are undergoing fiscal transformation through Diagnosis-Related Groups (DRG) as a prospective payment model to address rising costs and efficiency demands. Specific Background: Between 2016 and 2025, DRG-related research expanded alongside shifts from fee-for-service systems toward case-mix–based financing and value-based healthcare approaches. Knowledge Gap: Despite numerous empirical studies, there is limited macro-level intellectual mapping of global research trends, collaboration patterns, and thematic evolution in DRG and health payment reform literature. Aims: This study aims to map global scientific publications, identify key contributors, and analyze thematic structures and research trends using bibliometric methods. Results: Based on 143 Scopus-indexed articles analyzed באמצעות VOSviewer, publication output increased significantly, peaking in 2025, with the United States and China as dominant contributors. Four major thematic clusters were identified: hospital operational efficiency, macro-level financing policy, organizational adaptation, and healthcare quality and outcomes. The findings also reveal a post-pandemic shift toward integrating cost control with clinical quality and outcome-based evaluation. Novelty: This study provides a comprehensive bibliometric visualization of DRG research evolution, highlighting interdisciplinary linkages and emerging research directions. Implications: The results offer strategic insights for policymakers, healthcare administrators, and researchers to support transparent, efficient, and quality-oriented prospective payment systems and guide future research development. Highlights: Publication growth accelerated sharply, reaching the highest volume in 2025. Four thematic clusters define the intellectual structure of the field. Research focus shifts toward integrating cost management with clinical quality outcomes. Keywords: Bibliometric, Case-Mix, Diagnosis-Related Groups, Health Payment Reform, Hospital Efficiency